2019
DOI: 10.1111/ced.13959
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome patterns in hidradenitis suppurativa: support for the role of antimicrobial peptides and interferon pathways in disease pathogenesis

Abstract: Background. Hidradenitis suppurativa (HS) is a recurrent inflammatory disease of the apocrine sweat glands. Immune dysregulation probably contributes to the pathogenesis of HS. Aim. To harness mRNA expression arrays to investigate the transcriptome profile in HS compared with control skin. Methods. Illumina â HumanHT-12 v4 Expression BeadChips were used to measure mRNA expression in skin samples from HS (n = 10) and abdominoplasty (n = 11) skin specimens. Differentially expressed genes were detected by fitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 19 publications
1
42
1
Order By: Relevance
“…Third, generation of ORSCs seems a useful and relevant model to understand the pathophysiology of HS. The transcriptomic profile of these cells revealed pathways similar to previous reports from our group and others showing enrichment for keratinocyte differentiation, epidermis development pathways (8,35), and upregulation of IFN pathways (36,37) on whole skin isolated from HS lesions. Finally, recent studies have identified a phenotypic heterogeneity in HS patients, suggesting heterogeneous pathogenic pathways.…”
Section: Methodssupporting
confidence: 83%
“…Third, generation of ORSCs seems a useful and relevant model to understand the pathophysiology of HS. The transcriptomic profile of these cells revealed pathways similar to previous reports from our group and others showing enrichment for keratinocyte differentiation, epidermis development pathways (8,35), and upregulation of IFN pathways (36,37) on whole skin isolated from HS lesions. Finally, recent studies have identified a phenotypic heterogeneity in HS patients, suggesting heterogeneous pathogenic pathways.…”
Section: Methodssupporting
confidence: 83%
“…It is important to note that our study is the first to our knowledge to focus on a clinically homogenous group of patients with Hurley stage I. This might explain differences with previous studies, which involved patients with variable and often severe HS lesions ( 10 , 12 , 14 , 15 ). Our immune profiling of PBMCs from patients with HS highlighted higher frequencies of NK cells expressing granzyme B and perforin and producing IFN-γ upon stimulation ( Supplemental Figure 2, B–D ).…”
Section: Discussionmentioning
confidence: 78%
“…TNF-α is also frequently induced in advanced HS lesions, and the TNF-α blocker adalimumab had a positive effect on the clinical outcome of moderate-to-severe HS ( 9 ). Infiltrating myeloid cells are typically found in skin lesions, with antimicrobial peptide and IFN signatures reflecting the generation of potent innate immune responses to infection ( 6 , 10 15 ). An aberrant activation of neutrophils and B cells was also reported, which may jointly contribute to perpetuate lesion inflammation in patients with HS ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, immune responses to neutrophil and NET-related antigens have been linked to enhanced immune dysregulation and inflammation (35). In combination with the strong type I IFN signature in HS skin, these findings suggest a key involvement of the innate immune response in the pathogenesis of HS (36). As healing from the remarkable inflamation progresses, tunneling and scarring of the tissue occur (27,28,31).…”
Section: Inflammatory Pathways In Hidradenitis Suppurativamentioning
confidence: 99%